2020
DOI: 10.7554/elife.52976
|View full text |Cite
|
Sign up to set email alerts
|

Selective egg cell polyspermy bypasses the triploid block

Abstract: Polyploidization, the increase in genome copies, is considered a major driving force for speciation. We have recently provided the first direct in planta evidence for polyspermy induced polyploidization. Capitalizing on a novel sco1-based polyspermy assay, we here show that polyspermy can selectively polyploidize the egg cell, while rendering the genome size of the ploidy-sensitive central cell unaffected. This unprecedented result indicates that polyspermy can bypass the triploid block, which is an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Angiosperms are unique to produce the two adjacent dimorphic female gametes, the egg and central cells (Li and Yang, 2020 ). Polyspermy in the egg cell risks the production of a sterile triploid plant in return for the chance of polyploidization and speciation (Toda et al, 2016 ; Nakel et al, 2017 ; Mao et al, 2020 ). Although the central cell gives rise to the nutritious endosperm after fertilization and does not contribute to the genome of the next generation, polyspermy in the central cell results in a paternal and maternal genome imbalance in the endosperm and disturbs normal seed development (Scott et al, 2008 ; Köhler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiosperms are unique to produce the two adjacent dimorphic female gametes, the egg and central cells (Li and Yang, 2020 ). Polyspermy in the egg cell risks the production of a sterile triploid plant in return for the chance of polyploidization and speciation (Toda et al, 2016 ; Nakel et al, 2017 ; Mao et al, 2020 ). Although the central cell gives rise to the nutritious endosperm after fertilization and does not contribute to the genome of the next generation, polyspermy in the central cell results in a paternal and maternal genome imbalance in the endosperm and disturbs normal seed development (Scott et al, 2008 ; Köhler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vitro fertilization studies using isolated egg cells and sperm cells of maize ( Zea mays ) revealed that the fertilized egg cell is unable to fuse with additional sperm cells, possibly by cell wall formation following a calcium ion influx (Faure et al, 1994 ; Kranz et al, 1995 ; Antoine et al, 2000 ). Although triploid plants can be generated in vitro and in planta in several plant species due to polyspermy of the egg cell, they rarely occur under natural conditions (Toda et al, 2016 ; Grossniklaus, 2017 ; Nakel et al, 2017 ; Mao et al, 2020 ). Meanwhile, the polyspermy block mechanism in the central cell has not been studied directly to date.…”
Section: Introductionmentioning
confidence: 99%
“…Study with the polyspermic tetraspore (tes) mutant has suggested that polyspermy block exists in egg, but not in central cell (Scott et al, 2008). Other reports suggest that the egg cell can also fuse with two sperms to form triploid embryo with the central cell fuses with one sperm cell (Grossniklaus, 2017;Mao et al, 2020). Another distinction between the central cell and the egg cell is that plasma membrane fusion with sperm can trigger central cell mitotic division, suggesting signaling link between plasmogamy and activation of the nuclear division (Aw et al, 2010).…”
Section: Distinction Between Central Cell and Egg Cell In Fusion Withmentioning
confidence: 99%
“…Angiosperms are unique to produce the two adjacent dimorphic female gametes, the egg and central cells (Li and Yang, 2020). Polyspermy in the egg cell risks the production of a sterile triploid plant in return for the chance of polyploidization and speciation (Toda et al, 2016;Nakel et al, 2017;Mao et al, 2020). Although the central cell gives rise to the nutritious endosperm after fertilization and does not contribute to the genome of the next generation, polyspermy in the central cell results in a paternal and maternal genome imbalance in the endosperm and disturbs normal seed development (Scott et al, 2008;Köhler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vitro fertilization studies using isolated egg cells and sperm cells of maize (Zea mays) revealed that the fertilized egg cell is unable to fuse with additional sperm cells, possibly by cell wall formation following a calcium ion influx (Faure et al, 1994;Kranz et al, 1995;Antoine et al, 2000). Although triploid plants can be generated in vitro and in planta in several plant species due to polyspermy of the egg cell, they rarely occur under natural conditions (Toda et al, 2016;Grossniklaus, 2017;Nakel et al, 2017;Mao et al, 2020). Meanwhile, the polyspermy block mechanism in the central cell has not been studied directly to date.…”
Section: Introductionmentioning
confidence: 99%